Successful Management of Esophageal Perforation with Self-Expandable Metal Stent following Pneumatic Dilation for Achalasia Cardia - Verma, Abhai; Mohindra, Samir; Saraswat, Vivek Anand; Ghoshal, Uday Chand (Journal of Digestive Endoscopy, 2019)
Achalasia cardia is the most common cause of motor dysphagia. Pneumatic dilation (PD) of lower esophageal sphincter remains the cornerstone of treatment. However, it is associated with esophageal perforation in some cases. We present a case of esophageal perforation following PD of achalasia cardia which was successfully managed with esophageal stent.
Keywords: achalasia cardia; perforation; pneumatic dilation